Combined Biologic and Immunomodulatory Therapy is Superior to Monotherapy for Decreasing the Risk of Inflammatory Bowel Disease-Related Complications. (10th July 2020) - Targownik, Laura E; Benchimol, Eric I; Bernstein, Charles N; Singh, Harminder; Tennakoon, Aruni; Zubieta, Antonio Aviña; Coward, Stephanie; Jones, Jennifer; Kaplan, Gilaad G; Kuenzig, M Ellen; Murthy, Sanjay K; Nguyen, Geoffrey C; et al.
Abstract: Background and Aims: The combination of infliximab and azathioprine is more efficacious than either therapy alone for Crohn's disease [CD] and ulcerative colitis [UC]. However, it is uncertain whether these benefits extend to real-world clinical practice and to other combinations of biologics and immunomodulators. Methods: We collected health administrative data from four Canadian provinces representing 78 413 patients with inflammatory bowel disease [IBD] of whom 11 244 were prescribed anti-tumour necrosis factor [anti-TNF] agents. The outcome of interest was the first occurrence of treatment failure: an unplanned IBD-related hospitalization, IBD-related resective surgery, new/recurrent corticosteroid use or anti-TNF switch. Multivariable Cox proportional hazards modelling was used to assess the association between the outcome of interest and receiving combination therapy vs anti-TNF monotherapy. Multivariable regression models were used to assess the impact of choice of immunomodulator or biologic on reaching the composite outcome, and random effects generic inverse variance meta-analysis of deterministically linked data was used to pool the results from the four provinces to obtain aggregate estimates of effect. Results: In comparison with anti-TNF monotherapy, combination therapy was associated with a significant decrease in treatment ineffectiveness for both CD and UC (CD: adjusted hazard ratio [aHR] 0.77, 95% confidence interval [CI] 0.66–0.90; UC: aHR 0.72, 95% CI 0.62–0.84). Combination therapy was equally effective for adalimumab and infliximab in CD. In UC azathioprine was superior to methotrexate as the immunomodulatory agent (aHR = 1.52 [95% CI 1.02–2.28]) but not CD (aHR = 1.22 [95% CI 0.96–1.54]). Conclusion: In an analysis of a database of real-world patients with IBD, combination therapy decreased the likelihood of treatment failure in both CD and UC.